Effect of cooling and CMT mode process on additive manufacturing. Issue 11 (18th August 2022) - Wu, Wei; Xu, Wei; Xue, Jiaxiang; Yao, Ping
ABSTRACT: Cold metal transfer (CMT) additive manufacturing (AM) is widely used for its efficiency and low cost, in order to improve the efficiency the manufacturing, this study carried out CMT arc modes and interlayer cooling time depositions, and researched deposition stability, roughness, microstructure, and properties. Moreover, as the tensile anisotropy was a significant characteristic of arc AM, this study conducted tensile fracture metallographic test, and revealed the tensile anisotropic mechanism. The results showed that CMT mode was the most stable process, and CMT Plus Pulse (CMT+P) mode with an alternating of CMT and pulse processes had a finer grain and bigger hardness. Although an interlayer cooling time refined the grain size, it also increased the deposited time and roughness. Then, deposition efficiency of CMT+P continuous deposition was up to 87.9%, which realized the forming efficiency. The tensile fracture metallographic test indicated the deformed columnar grains were widened by horizontal stretching, and then the fracture occurred at the grain boundaries. However, no obvious grain deformation occurred under the vertical tension, and the columnar grain boundaries were the weak link of tensile fatigue. Thus, horizontal tensile strength with more grain boundaries was smaller than the vertical one.